Tropical modernism in Léopoldville ans decolonization. Case study of Lovanium by Marcel Boulengier - Alexis Tshiunza; André Ockerman; Jonathan Nkondi (Festival dell'Architettura Magazine)
In 1949, the Belgian Congo benefited from a major development program called the ten-year plan. But the policy of segregation is strongly encouraged. Nevertheless, in 1950, architect Marcel Boulengier (1909-1976) is asked to draw a general plan for the construction of an interracial University. After careful examination of the plan, several detailed adjustments were made in order to avoid any segregation. Many Belgians rightly thought that this project would accelerate independence. The article examines how the architecture and urban planning proposed for this project built on an uninhabited site reflects decolonization and even indigenization.